Indications and Neonatal Outcomes of Caesarean Delivery among Women Attending Maternity Teaching Hospital, Sulaimaniyah City, Iraq - Faris, Gona Othman (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Cesarean section is the most commonly performed surgical procedure in obstetrics, defined as the birth of a fetus via a surgically created incision in the anterior uterine wall. Over the past two decades, there has been a steady rise in the rate of cesarean section delivery globally. As a result, short-term and long-term maternal and neonatal complications are rising. Objective: This study aimed to investigate the indications and neonatal outcomes of CS among women attending the Maternity Teaching Hospital in Sulaimaniyah city, Iraq. Materials and Methods: This descriptive cross-sectional research was performed on 100 women from 12th December 2021 to 12th April 2022. Results: Among participants, 50% were aged >30 years, and three-quarters were housewives. Nearly half of the mothers were multigravida and multipara, in which 64% were emergency, but only 10% underwent CS after delivery induction failure. The utmost common indications of CS were preeclampsia (16%), followed by meconium-stained liquor (12%), non-reassuring fetal heart rate pattern (10%), malpresentation, malposition, and previous C/S (8%). In most newborn babies, Apgar score level was seven and <7 minutes. Conclusions: Most CS were emergency and performed for babies at full and post-term. NICU admission was associated with a low Apgar score, respiratory distress syndrome and all indications of CS.
Keywords: Indications; neonatal out comes; emergency caesarean delivery; labour failure; descriptive cross sectional study